Yarn Properties of Blended Fiber Pineapple Leaf Fiber/Cotton - Azihar, Alis Alia; Roslan, Mohd Nazrul (Progress in Engineering Application and Technology, 2023)
Yarns with natural fibers are becoming increasingly popular with the increase in environmental awareness. This is mainly because the hybridization of fiber may reduce the use of synthetic fibers in the making of yarns. Note that cotton currently dominates the natural textile industry all over the world. On the other hand, pineapple leaf fiber (PALF) has been proven to be biodegradable and compatible with the environment. This study observed the properties of cotton fiber with different compositions of PALF. The physical and mechanical analyses such as surface morphology, fineness of sliver and yarn, and tensile strength test were conducted on yarn. Apart from that, the morphology analysis of different PALF compositions was observed through Optical Microscope (OM). At the beginning of this study, the optimum characteristics of PALF/cotton slivers subjected to the different compositions of PALF were determined. The finding demonstrated that the yarn characteristics could be effectively controlled by varying the PALF composition. Following this, PALF/cotton yarn of three different weight ratios was developed (50:50, 40:60 and 30:70). The findings showed that the physical and mechanical properties of sliver and yarn could be effectively controlled by varying PALF composition. The composition of 30% PALF exhibited excellent physical properties. It was noted that the 50% PDF and 40% PALF had improved in mechanical properties. Nevertheless, the subsequent increase in the composition of PALF did not increase the strength of the yarn.